Pengaruh Kondisi Lingkungan Keluarga Terhadap Kepatuhan Tata Tertib Siswa Kelas V SD Negeri 101796 Patumbak - Tri Ulina Br Sembiring (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2021)
This study aims to identify the influence of family environment conditions on the compliance with school rules among fifth-grade students at SD Negeri 101796 Patumbak. Using a correlational quantitative method, the research involved 54 students as subjects. Data were collected through questionnaires and analyzed using SPSS 22. The findings revealed a significant positive relationship between the conditions of the family environment and the students' compliance with school rules. Approximately 33.3% of the variance in rule compliance was explained by family environment variables. The study suggests the importance of family roles in supporting student discipline at school.